Electrical and electronic principles and technology - Bird, John (Newnes, 2007)
In this book John Bird introduces electrical principles and technology through examples rather than theory - enabling students to develop a sound understanding of the principles needed by technicians in fields such as electrical engineering, electronics and telecommunications. No previous background in engineering is assumed, making this an ideal text for vocational courses at Level 2 and 3, foundation degree and introductory courses for undergraduates. The book presents a logical topic progression rather than following the structure of a particular syllabus. However, the coverage of this new edition has been brought fully in line with the electrical and electronics units of the 2007 BTEC National specification. It is also designed to cover the requirements of the BTEC First specifications. New material in this third edition includes brand new chapters on semiconductor diodes and transistors as well as added sections on batteries, fuel cells and alternative and renewable energies, relative and absolute voltages, self and mutual inductance, and virtual test and measuring instruments.